Determinants of Muzakki Decision to Pay Agricultural Zakat Through Institutions in West Java - Deni Lubis; Awiwin Awiwin; Yekti Mahanani (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
In Indonesia, agricultural zakat collection is very low in comparison to its potential, while the majority of the population works in agricultural sector. Thus, it is crucial to conduct research on this matter. This study aims to investigate the factors that influence muzakki to pay agricultural zakat through institutions in Indramayu, West Java. Using Roscoe’s model, 70 farmers who had reached the nishab were determined as sample. The data were analyzed using a logistic regression analysis approach. The findings show that four variables have a significant impact on decision of the farmers to pay agricultural zakat through institution, namely religiosity, zakat comprehension, awards or appreciation, and service quality. Institutions should be innovative in order to maximize agricultural zakat collection, such as providing zakat pick-up service and a zakat activity report for muzakki on a regular basis. Furthermore, in order to convey the significance and benefits of paying zakat through institutions, institutions must strengthen their collaboration with local authorities and religious leaders.======================================================================================================== ABSTRAK – Determinan yang Mempengaruhi Muzakki Membayar Zakat melalui Lembaga Amil di Jawa Barat. Walaupun berstatus sebagai negara agraris, pengumpulan zakat pertanian di Indonesia sangat kecil dibandingkan dengan potensinya. Oleh karena itu, kajian tentang masalah ini sangat penting untuk dilakukan. Penelitian ini bertujuan untuk mengkaji faktor-faktor yang mempengaruhi muzakki membayar zakat pertanian melalui lembaga amil. Dengan menggunakan model pengambilan sampel Roscoe, sebanyak 70 petani yang telah mencapai nishab dipilih sebagai responden. Data penelitian diolah dengan pendekatan logistic regression analysis. Hasil penelitian menunjukkan bahwa ada empat variabel yang berpengaruh signifikan dalam keputusan petani dalam membayar zakat pertanian melalui lembaga amil, yaitu religiositas, pemahaman zakat, penghargaan atau apresiasi, dan kualitas pelayanan. Dalam rangka optimalisasi penghimpunan zakat pertanian, lembaga-lembaga penghimpun zakat melakukan inovasi pelayanan seperti penyediaan layanan jemput zakat dan pelaporan penggunaan zakat secara berkala. Selain itu, juga perlu dilakukan kerjasama dengan tokoh-tokoh agama dan pemerintah setempat dalam memberikan pemahaman dan kesadaran tentang manfaat dan pentingnya berzakat melalui lembaga amil.